2008
DOI: 10.1039/b719943k
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of electron diffusion coefficient in organic and inorganic semiconductors with broad distributions of states

Abstract: The carrier transport properties in nanocrystalline semiconductors and organic materials play a key role for modern organic/inorganic devices such as dye-sensitized (DSC) and organic solar cells, organic and hybrid light-emitting diodes (OLEDs), organic field-effect transistors, and electrochemical sensors and displays. Carrier transport in these materials usually occurs by transitions in a broad distribution of localized states. As a result the transport is dominated by thermal activation to a band of extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
178
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 144 publications
6
178
0
1
Order By: Relevance
“…The above mentioned conduction mechanism is highly sensitive to the kinetics of trapping/release of trapped electrons at PCBM molecules. While the inclusion of fast traps does not modify the carrier conductivity [16], slow trapping would have large influence on the transport mechanisms producing conductivity changes. It is worth noting that similarity of 1 R values at forward bias allows discarding morphology effects as originating the 1 R differences observed.…”
Section: Resultsmentioning
confidence: 95%
“…The above mentioned conduction mechanism is highly sensitive to the kinetics of trapping/release of trapped electrons at PCBM molecules. While the inclusion of fast traps does not modify the carrier conductivity [16], slow trapping would have large influence on the transport mechanisms producing conductivity changes. It is worth noting that similarity of 1 R values at forward bias allows discarding morphology effects as originating the 1 R differences observed.…”
Section: Resultsmentioning
confidence: 95%
“…This value exceeds by ∌1000 times the largest values previously reported for DSC photoanodes. 4,41 The plausibility of this value may be weighed against the theoretically predicted diffusion coefficient for polycrystalline ZnO. Equation 7 can also be expressed as 41…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, hopping systems can also be reduced to the multiple trapping model by using the concept of transport energy. [8,9,17] Next, we introduce some magnitudes that enter the expression of impedance. [4] First, the chemical capacitance is defined as follows [Eq.…”
Section: Kinetic Model and Interpretation Of Kinetic Constantsmentioning
confidence: 99%
“…A full theory that rationalizes the interpretation of measured coefficients and their relation to stochastic simulations was formulated thereafter. [5,8,9] In addition, it was shown that nonlinear recombination is the rule in systems such as DSCs and organic solar cells, [3,10,11] and such a nonlinear feature enhances inhomogeneous behavior. [12] In this paper, we provide a more general derivation of the impedance model that includes the trapping factors and that uses a nonlinear recombination rate.…”
Section: Introductionmentioning
confidence: 99%